Stability and Vulnerability of the Latin American Middle Class - Torche, Florencia; Lopez-Calva, Luis F. (Taylor and Francis, 2013)
Using panel data-sets from Mexico and Chile for the first years of the 21st century, the authors examine the determinants of middle-class intra-generational mobility. The middle class is defined by means of a latent index of economic well-being that is less sensitive to short-term fluctuation and measurement error than standard measures of income. The authors find high rates of both upward and downward mobility in Mexico and Chile, indicating that the middle class has opportunities to move to higher levels of well-being but is also vulnerable to falling into poverty. In both countries, labour-market resources (education and occupational status of the household head and number of members in the labour market) are much stronger determinants of mobility than demographic factors, suggesting the importance of policies that foster human capital and protect workers from shocks. Rural middle-class households are substantially more vulnerable to falling into poverty and have little chance of advancing to upper classes than their urban counterparts.